HRD as the epicentre of governance in public administration - Sousa, M. (The future of HRD, 2020)
This chapter describes and analyses governance in public administration making a proposal of a model for human resource development (HRD) as the nucleus of governance. The scope is to explore which are the more relevant research concepts of the HRD dimension of a governance model in public administration and to evaluate which model of HRD dimension of governance best fits public administration. The chapter offers a number of recommendations on how to promote the participation of the workers, and the delegation of responsibilities, in line with new public management principles. The main findings could also help organisations to transform their processes and contribute to higher efficiency and effectiveness of public organisations.